2013
DOI: 10.1103/physrevb.87.241102
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of magnetic interactions in a pressure-induced Jahn-Teller driven magnetic dimensionality switch

Abstract: We present the results of high-field magnetization and muon-spin relaxation measurements on the coordination polymer CuF2(H2O)2(pyrazine) in pressures up to 22.5 kbar. We observe a transition from a quasi-two-dimensional to a quasi-one-dimensional antiferromagnetic phase at 9.1 kbar, driven by a rotation of the Jahn-Teller axis. Long-range antiferromagnetic ordering is seen in both regimes, as well as a phase separation in the critical pressure region. The magnetic dimensionality switching as pressure is incre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 21 publications
5
44
0
Order By: Relevance
“…In addition, the method can be applied in bulky sample environments such as pressure cells [24,25]. In our experiments, we used powdered solution-grown PHCC polycrystalline samples of typical mass 800 mg.…”
mentioning
confidence: 99%
“…In addition, the method can be applied in bulky sample environments such as pressure cells [24,25]. In our experiments, we used powdered solution-grown PHCC polycrystalline samples of typical mass 800 mg.…”
mentioning
confidence: 99%
“…8 Quantum magnets built from organic molecules can be very susceptible to perturbation by external pressure due to their 'soft' molecular frameworks. 9 This paper is concerned with the S = 1/2 quasi-two-dimensional gapped quantum antiferromagnet piperazinium hexachlorodicuprate [(C 4 H 12 N 2 )Cu 2 Cl 6 , hereafter PHCC]. PHCC crystallizes in the triclinic space group P1 with lattice parameters 10 a = 7.984(4)Å, b = 7.054(4)Å, c = 6.104(3)Å, α = 111.23 (8) • , β = 99.95 (9) • , γ = 81.26 (7) • .…”
Section: Introductionmentioning
confidence: 99%
“…9 This paper is concerned with the S = 1/2 quasi-two-dimensional gapped quantum antiferromagnet piperazinium hexachlorodicuprate [(C 4 H 12 N 2 )Cu 2 Cl 6 , hereafter PHCC]. PHCC crystallizes in the triclinic space group P1 with lattice parameters 10 a = 7.984(4)Å, b = 7.054(4)Å, c = 6.104(3)Å, α = 111.23 (8) • , β = 99.95 (9) • , γ = 81.26 (7) • . The spin-1/2 Cu 2+ ions are connected by a complex layered network (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…An added advantage of molecular systems is the ability to make controlled adjustments to the crystal structure, thereby tuning interaction strengths and better testing the predictions of the SLHAFM and associated models. To this end, we and others have previously shown that it is possible to gain a degree of control over the primary exchange energy in low-dimensional molecular antiferromagnets via constitutional changes that include deuteration 18 , anion substitution 11,19 , exchange of halide ligands 20,21 , and the application of high pressures 22,23 .…”
Section: Introductionmentioning
confidence: 99%